Experimental and Field Data Support Range Expansion in an Allopolyploid Arabidopsis Owing to Parental Legacy of Heavy Metal Hyperaccumulation - Paape, Timothy; Akiyama, Reiko; Cereghetti, Teo; Onda, Yoshihiko; Hirao, Akira S.; Kenta, Tanaka; Shimizu, Kentaro K. (Frontiers in Genetics, 2020)
Empirical evidence is limited on whether allopolyploid species combine or merge parental adaptations to broaden habitats. The allopolyploid Arabidopsis kamchatica is a hybrid of the two diploid parents A. halleri and A. lyrata. Arabidopsis halleri is a facultative heavy metal hyperaccumulator, and may be found in cadmium (Cd) and zinc (Zn) contaminated environments, as well as non-contaminated environments. Arabidopsis lyrata is considered non-tolerant to these metals, but can be found in serpentine habitats. Therefore, the parents have adaptation to different environments. Here, we measured heavy metals in soils from native populations of A. kamchatica. We found that soil Zn concentration of nearly half of the sampled 40 sites was higher than the critical toxicity level. Many of the sites were near human construction, suggesting adaptation of A. kamchatica to artificially contaminated soils. Over half of the A. kamchatica populations had > 1,000 g g–1 Zn in leaf tissues. Using hydroponic treatments, most genotypes accumulated > 3,000 g g–1 Zn, with high variability among them, indicating substantial genetic variation in heavy metal accumulation. Genes involved in heavy metal hyperaccumulation showed an expression bias in the A. halleri-derived homeolog in widely distributed plant genotypes. We also found that two populations were found growing on serpentine soils. These data suggest that A. kamchatica can inhabit a range of both natural and artificial soil environments with high levels of ions that either of the parents specializes and that it can accumulate varying amount of heavy metals. Our field and experimental data provide a compelling example of combining genetic toolkits for soil adaptations to expand the habitat of an allopolyploid species.